Characterization and effective expansion of CD4−CD8− TCRαβ+ T cells from individuals living with type 1 diabetes - J. Ernesto Fajardo-Despaigne; Félix Lombard-Vadnais; Adam-Nicolas Pelletier; Aïnhoa Olazabal; Lucie Boutin; Sarah Pasquin; Valérie Janelle; Laurent Legault; Jean-Sébastien Delisle; Erin E. Hillhouse; Lise Coderre; Sylvie Lesage (Molecular Therapy: Methods & Clinical Development)
CD4−CD8− TCRαβ+ (double-negative [DN]) T cells represent a rare T cell population that promotes immunological tolerance through various cytotoxic mechanisms. In mice, autologous transfer of DN T cells has shown protective effects against autoimmune diabetes and graft-versus-host disease. Here, we characterized human DN T cells from people living with type 1 diabetes (PWT1D) and healthy controls. We found that while DN T cells and CD8+ T cells share many similarities, DN T cells are a unique T cell population, both at the transcriptomic and protein levels. We also show that by using various cytokine combinations, human DN T cells can be expanded in vitro up to 1,000-fold (mean >250-fold) and remain functional post-expansion. In addition, we report that DN T cells from PWT1D display a phenotype comparable to that of healthy controls, efficiently expand, and are highly functional. As DN T cells are immunoregulatory and can prevent T1D in various mouse models, these observations suggest that autologous DN T cells may be amenable to therapy for the prevention or treatment of T1D.